EXPLORING THE PROBLEMS FACED BY NON-ENGLISH LECTURERS OF UNIVERSITAS RIAU KEPULAUAN ON USING MACHINE TRANSLATION ON ACADEMIC PURPOSE - ERWIN ASHARI; Shalehoddin Shalehoddin (English Department, University of Riau Kepulauan, Batam,Indonesia, 2019)
The aim of this study is to measure the difficulties faced by Non- English lecturers of universitas riau kepulauan on using machine translation on writing article. It is a qualitative research by using descriptive analysis. Questionnaire was used to collect data; the questionnaire was shared to all lecturers of Riau Kepulauan University, as the respondents. Based on the questionnaires, it was found that there are some difficulties such as idiom, not accordance with the principle of translation and sometimes the word cannot be found on the google translation